9,9-Bis[4-(prop-2-ynyloxy)phenyl]-9H-fluorene - Shah, K.; Shah, M.R.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(31)H(22)O(2), the bond angle at the C atom belonging to the five-membered ring of the fluorene system is opened to 112.64 (12)degrees. The two benzene rings are twisted with respect to the fluorene ring system at dihedral angles of 72.81 (6) and 81.83 (6)degrees. One C(aryl)-O-C-C[triple-bond] fragment is extended, with a C-O-C-C torsion angle of -178.77 (13)degrees, but the other C(aryl)-O-C-C[triple-bond] fragment is bent, with a C-O-C-C torsion angle of 64.78 (19)degrees. Intermolecular weak C-H...O hydrogen bonding is present in the crystal structure.